Silver-enhanced fluorescence of bimetallic Au/Ag nanoclusters as ultrasensitive sensing probe for the detection of folic acid - Fereja, Shemsu Ligani; Li, Ping; Guo, Jinhan; Fang, Zhongying; Zhang, Ziwei; Zhuang, Zhihua; Zhang, Xiaohui; Liu, Kaifan; Chen, Wei (Talanta (Oxford), 2021)
Folic acid (FA) is the natural form of water-soluble vitamins widely found in most plants and animal products and its deficiency leads to several human body abnormalities. The advancements of metal nanoclusters are highly increasing due to their molecule-like optical properties and attractive applications. Because of increasingly demand of noble metal nanoclusters as sensing templates, different synthesis methods have been developed for facile synthesis of noble metal nanoclusters. Herein, red-emitting fluorescent bovine serum albumin (BSA)-capped Au–Ag bimetallic NCs are facilely synthesized through green one-pot synthetic approach. The effect of silver on the fluorescence properties of Au NCs was investigated and it was found that introduction of silver can enhance the fluorescence intensity. The fluorescence intensity of the as-prepared Au–Ag nanoclusters gets quenched in the presence of folic acid in an aqueous medium and it was used as ultrasensitive sensing probe for FA detection. The developed Au–Ag NCs-based sensing probe shows linear response in the wide range of 0–100 μM and the detection limit is as low as 0.47 nM. Its applicability has also been confirmed successfully in real human serum, urine and FA tablet samples. Due to the high stability, sensitivity and selectivity, the developed bimetallic cluster sensing system is highly promising to be applied in the pharmaceutical and clinical laboratories. [Display omitted] •Au–Ag fluorescent sensing probe for the sensitive detection of folic acid was developed.•The effect of silver on the fluorescence properties of Au NCs has been investigated.•The fluorescence of bimetallic nanoclusters was quenched by folic acid.•The developed fluorescence system can be used for folic acid detection in the human serum, urine and commercial FA tablet.